Laesio enormis in Serbian law and its relationship with other related legal institutes - Dabić-Nikićević Snežana (Anali Pravnog Fakulteta u Beogradu)
Mihailo Konstantinović raised important issues regarding how laesio enormis should be applied and regulated in the future, given the inconsistency in the post-war judicial practice. Konstantinović supported the view that laesio enormis should be governed by an objective principle. However, in the Law on Obligations, the right to annul the contract due to obvious disparity between contract obligations exists only if the aggrieved party was mistaken about the true value of the performance when concluding the contract. In this paper, the author raises the question whether such a shift in the regulation of laesio enormis represents an improvement or serious arguments can be raised against it. The author first analyzes how laesio enormis is regulated in comparative law, and then discusses the pros and cons of regulating this legal institute according to an objective and subjective principle.